Soil bacterial diversity and community structure of Suaeda glauca vegetation in the Hetao Irrigation District, Inner Mongolia, China - Dong, Ruixiao; Wang, Xinbo; Li, Yuyi; Zhang, Hongyuan; Li, Xiaobin; Song, Jiashen; Chang, Fangdi; Feng, Wenhao; Pang, Huancheng; Wang, Jing (Frontiers in Microbiology, 2024)
Exploring the bacterial community in the S. glauca rhizosphere was of great value for understanding how this species adapted to the saline-alkali environment and for the rational development and use of saline-alkali soils. In this study, high-throughput sequencing technology was used to investigate the diversity characteristics and distribution patterns of soil bacterial communities in the rhizosphere of S.glauca-dominated communities in the Hetao Irrigation Distract, Inner Mongolia, China. The relationships among bacterial characteristics, soil physicochemical properties and vegetation in four sampling sites were analyzed. The soil bacterial communities in the rhizosphere of S. glauca-dominated communities were mainly composed of 16 phyla (i.e., Proteobacteria, Actinobacteria, Bacteroidetes, Gemmatimonadetes, Chloroflexi, Acidobacteria, Firmicutes, Planctomycetes, Deinococcus-Thermus, Verrucomicrobia, Saccharibacteria, Cyanobacteria, Nitrospirae, JL-ETNP-Z39, Parcubacteria and Chlorobi), and these populations accounted for more than 99% of the total bacterial community. At the genus level, the main bacterial communities comprised Halomonas, Nitriliruptor, Euzebya and Pelagibius, which accounted for 15.70% of the total bacterial community. An alpha diversity analysis indicated that the richness and diversity of rhizosphere soil bacteria differed significantly among the sampling sites, and the bacterial richness and diversity indices of severe saline-alkali land were higher than those of light and moderate saline-alkali land. The principal component analysis (PCA) and linear discriminant analysis effect size (LEfSe) showed significant differences in the species composition of the rhizosphere soil bacterial community among different sampling sites. A correlation analysis showed that the number of bacterial species exhibited the highest correlation with the soil water content (SWC). The richness and evenness indices were significantly correlated with the SWC and SO42–, K+ and Mg2+ concentrations. The electrical conductivity (EC), soluble ions (Na+, CO32– + HCO3–, K+, Ca2+, Mg2+, and SO42+), SWC and vegetation coverage (VC) were the main drivers affecting the changes in its community structure. The bacterial community in the rhizosphere of S. glauca enhanced the adaptability of S. glauca to saline-alkali environment by participating in the cycling process of nutrient elements, the decomposition of organic matter and the production of plant growth regulating substances. These results provided a theoretical reference for further study on the relationship among rhizosphere soil microorganisms and salt tolerance in halophytes.